Dengue Fever in the Darfur Area, Western Sudan - Ayman Ahmed; Yousif Ali; Babiker Elmagboul; Omaima Mohamed; Adel Elduma; Hind Bashab; Ahmed Mahamoud; Hayat Khogali; Arwa Elaagip; Tarig Higazi (Emerging Infectious Diseases, 2019)
We report an outbreak of dengue in Darfur, western Sudan, during September 2014–April 2015. Dengue virus–specific PCR testing of 50 samples from nonmalaria febrile illness case-patients confirmed 35 dengue cases. We detected 7 cases of dengue shock syndrome and 24 cases of dengue hemorrhagic fever.